Body mass index and vitamin D as risk factors for the development of uterine leiomyomas in Mexican women. Issue 1 (March 2022) - Huseman-Plascencia, Luz A; Villa-Villagrana, Francisco; Ballesteros-Manzo, Alberto; Baptista Rosas, Raúl C.; Mercado-Sesma, Arieh R; Arámbula-Chavolla, Mar I
Objective: The objective of the present study was to determine if body mass index and vitamin D levels are risk factors for the development of uterine leiomyomas in Mexican women. Methods: A cross-sectional study was designed. Inclusion criteria were women between 20 and 55 years with a suspect of uterine leiomyomas. Transvaginal ultrasonography was made to confirm the diagnosis and clinical variables were collected. Vitamin D levels were measured in serum by chemiluminescence immunoassay. Binary linear regression analysis was conducted to assess the predictors of uterine leiomyomas. Results: A total of 106 patients were evaluated, the mean age was 41.4 ± 8.0 years. The serum levels of vitamin D were insufficient in 94 (88.7%) and 82 (77.3%) has overweight or obesity. However, only 50 (47.2%) of participants have a diagnostic of uterine leiomyomas. BMI not increased the probability of having insufficient levels of vitamin D or uterine leiomyomas. Only, age (> 45 years) and levels of vitamin D (<30 ng/mL) were predictors of uterine leiomyomas (OR 10.345, 95% CI 2.737–39.095; p  = 0.001; and OR 2.26, 95% CI 1.011–5.073; p  = 0.014), respectively. Conclusions: Insufficient levels of vitamin D are common in Mexican women. Age and hypovitaminosis D are possible risk factors in the development of uterine leiomyomas in Mexican women.